Yang/Qi Invigoration: An Herbal Therapy for Chronic Fatigue Syndrome with Yang Deficiency?. (11th February 2015) - Leong, Pou Kuan; Wong, Hoi Shan; Chen, Jihang; Ko, Kam Ming
Abstract : According to traditional Chinese medicine (TCM) theory, Yang and Qi are driving forces of biological activities in the human body. Based on the crucial role of the mitochondrion in energy metabolism, we propose an extended view of Yang and Qi in the context of mitochondrion-driven cellular and body function. It is of interest that the clinical manifestations of Yang/Qi deficiencies in TCM resemble those of chronic fatigue syndrome in Western medicine, which is pathologically associated with mitochondrial dysfunction. By virtue of their ability to enhance mitochondrial function and its regulation, Yang- and Qi-invigorating tonic herbs, such as Cistanches Herba and Schisandrae Fructus, may therefore prove to be beneficial in the treatment of chronic fatigue syndrome with Yang deficiency.